2019
DOI: 10.1002/hon.2622
|View full text |Cite
|
Sign up to set email alerts
|

Emerging translational science discoveries, clonal approaches, and treatment trends in chronic myeloproliferative neoplasms

Abstract: The 60th American Society of Hematology (ASH) held in San Diego in December 2018 was followed by the 13th Post‐ASH chronic myeloproliferative neoplasms (MPNs) workshop on December 4 and 5, 2018. This closed annual workshop, first introduced in 2006 by Goldman and Mughal, was organized in collaboration with Alpine Oncology Foundation and allowed experts in preclinical and clinical research in the chronic MPNs to discuss the current scenario, including relevant presentations at ASH, and address pivotal open ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 106 publications
0
14
0
Order By: Relevance
“…Each subtype showed both overlapping and progressively divergent transcriptional pathways, suggesting both a shared signature across all MPN, and unique biological trajectories. Pathway-enrichment analyses confirmed the existence of a shared inflammatory milieu 37,[77][78][79][80][81][82] among MPN. We also confirmed that the JAK1/ JAK2 inhibitor ruxolitinib was associated with inhibition of inflammatory as well as interferon-mediated signaling pathways.…”
Section: Discussionmentioning
confidence: 93%
“…Each subtype showed both overlapping and progressively divergent transcriptional pathways, suggesting both a shared signature across all MPN, and unique biological trajectories. Pathway-enrichment analyses confirmed the existence of a shared inflammatory milieu 37,[77][78][79][80][81][82] among MPN. We also confirmed that the JAK1/ JAK2 inhibitor ruxolitinib was associated with inhibition of inflammatory as well as interferon-mediated signaling pathways.…”
Section: Discussionmentioning
confidence: 93%
“…Each subtype showed both overlapping and progressively divergent transcriptional pathways, suggesting both a shared signature across all MPN, and unique biological trajectories. Pathway-enrichment analyses confirmed the existence of a shared inflammatory milieu (Barbui et al, 2011;Geyer et al, 2015;Hasselbalch and Bjorn, 2015;Koschmieder and Chatain, 2020;Marin Oyarzún and Heller, 2019;Mughal et al, 2019;Skov et al, 2011) among MPN. We also confirmed that the JAK1/JAK2 inhibitor ruxolitinib was associated with inhibition of inflammatory as well as interferon-mediated signaling pathways.…”
Section: Discussionmentioning
confidence: 87%
“…However, this has inherent limitations with regard to its lower limit of detection and quantification of BCR-ABL1 transcripts, problems which became important as TKI that were more powerful, compared to imatinib, were developed. 9 This, in turn, affected the definition and identification of deep molecular response (DMR), defined as a greater than 4 (MR4), 4.5 (MR4.5) or 5 (MR5) log reduction in BCR-ABL1 transcripts on the International Scale, below the standardized baseline ( Figure 2). DMR is now recognized to be of considerable clinical importance to prospectively identify Ferrata Storti Foundation patients likely to remain in remission after discontinuing TKI therapy.…”
Section: Clinically Validated Tests For Detecting and Monitoring Bcr-mentioning
confidence: 99%